2020
DOI: 10.1002/bab.1893
|View full text |Cite
|
Sign up to set email alerts
|

The effect of deoxyschizandrin on chronic unpredictable mild stress–induced depression

Abstract: The purpose of the present study was to evaluate the antidepressant effect of deoxyschizandrin (DEO) in chronic unpredictable mild stress (CUMS)–induced mice. The mice were subjected to CUMS paradigm for 8 weeks. From the sixth week, the mice were intragastrically treated with DEO once daily for continuous 3 weeks. The behavior tests including sucrose preference test (SPT), forced swimming test (FST), tail suspension test (TST), and open field test were conducted. Additionally, the expressions of TLR4, MyD88, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Our previous study demonstrated that leptin is essential for the effects of S. chinensis fruit extracts against MetS and NAFLD (Gu et al, 2020). Moreover, several studies have demonstrated that Schisandra chinensis , DS, and its analogues can alleviate diverse CNS diseases including depression, Parkinson's disease, Alzheimer's disease, etc (Ma et al, 2021; Yan et al, 2021; Zhang et al, 2018; Zhi et al, 2019). Therefore, we speculated that the effects of DS on anti‐MetS and satiety may be involved in hypothalamic activation of TGR5 and leptin signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study demonstrated that leptin is essential for the effects of S. chinensis fruit extracts against MetS and NAFLD (Gu et al, 2020). Moreover, several studies have demonstrated that Schisandra chinensis , DS, and its analogues can alleviate diverse CNS diseases including depression, Parkinson's disease, Alzheimer's disease, etc (Ma et al, 2021; Yan et al, 2021; Zhang et al, 2018; Zhi et al, 2019). Therefore, we speculated that the effects of DS on anti‐MetS and satiety may be involved in hypothalamic activation of TGR5 and leptin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have demonstrated that Schisandra chinensis, DS, and its analogues can alleviate diverse CNS diseases including depression, Parkinson's disease, Alzheimer's disease, etc (Ma et al, 2021;Yan et al, 2021;Zhang et al, 2018;Zhi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Further, PSD 95 is widely involved in the onset and treatment of cognitive and emotional related mental diseases. 57,58 Many studies have shown that protein expression of SYN 1 and PSD 95 are decreased in the prefrontal cortex of patients with major depression. A decrease of presynaptic SYN 1 and postsynaptic PSD 95 in the hippocampus and prefrontal cortex due to chronic stress may lead to depressive behavior and a severe decline in cognitive function in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Target gene prediction of miRNAs was performed using the Encyclopedia of RNA Interactomes (ENCORI, http://starbase.sysu.edu.cn/index.php ) [ 34 ]. GO and KEGG pathway analyses were performed using WEB-based Gene SeT AnaLysis Toolkit (WebGestalt, http://www.webgestalt.org/ ) [ 35 ].…”
Section: Methodsmentioning
confidence: 99%